10 Be exposure age for sorted polygons in the Sudetes Mountains - Engel, Zbyněk; Křížek, Marek; Braucher, Regis; Uxa, Tomáš; Krause, David (Permafrost and Periglacial Processes, 2021)
International audience Patterned-ground landforms represent the most common phenomenon of periglacial environment, and their large sorted forms belong to the few morphological indicators of past permafrost distribution. The relic forms of patterned ground are widespread on high-elevated surfaces in the central European uplands, providing the evidence of regional periglacial conditions in the last glacial period. However, the timing of theselandforms, as well as their potential for paleoclimate reconstructions, has remained unexplored. In this paper, we present 10 Be exposure ages from the large sorted polygons sampled at four sites in the Sudetes Mountains, the highest part of the central European uplands. These results indicate that these landforms started to form at the end of Marine Isotope Stage 3, and the main phase of their formation occurredbetween 30 and 20 ka. This research confirms the hypothesis of sorted patterned-ground formation within the last (Weichselian) glacial stage (110.6 – 11.7 ka) and suggests that earlier-sorted features are not preserved in the Sudetes. The recognized period of enhanced periglacial activity coincides with a prominent cold interval identified earlier in both regional and northern-hemispheric proxy records.Central Europe, cosmogenic-nuclide dating, past permafrost, patterned ground, periglacial environment, Quaternary